Pedagogical content knowledge (PCK) among pre-service teachers and their interest in the teaching of Arabic - Azizan, Nor Khalila; Mamat, Arifin; Sahrir, Muhammad Sabri (Faculty of Education, University of Malaya (UM), Kuala Lumpur, 2017)
Pedagogical content knowledge is a type of knowledge that is unique to teachers, and is based on the manner in which teachers relate their pedagogical knowledge to their subject matter knowledge. The study attempts to examine the perceived level of pre-service teachers’ readiness in term of pedagogical content knowledge (PCK) and their interest in the teaching of Arabic. The study employed a survey method to gather the data among purposively selected respondents of thirty (30) final year students of Bachelor Degree in Arabic Language with Education at Universiti Pendidikan Sultan Idris (UPSI), Malaysia. The study adapted several questionnaires as an instrument to collect the data. It was distributed to the respondents and analyzed using Statistical Package for Social Science (SPSS 17.0) software. The results are shown in simple descriptive statistical analysis; percentage, frequency, and mean scores which were used to interpret the data. The findings show that the readiness in terms of PCK among preservice teachers was at a medium level. Meanwhile, the result demonstrates a high level of interest in the teaching of Arabic language among pre-service teachers. The study also recommends some recommendations to further improve the performance of Bachelor Degree Arabic Language with Education pre-service teachers to enhance the level of readiness during teaching training period.